High prevalence of vitamin D deficiency and cancer in Saudi Arabian populations: Can we hypothesize a link?. Issue 2 (August 2015) - Nabi, Gowher; Hobani, Yahya; Sarwat, Maryam
Abstract Inspite of having so much sunshine, Saudi Arabian population is suffering from the deficiency of the 'sunshine vitamin', vitamin D, measured in the serum as 25-OHD level. According to a recent report, about 83.6% of Saudi population is vitamin D deficient. 31.9% have severe, 32% have moderate and 19.7% have mild vitamin D deficiency (VDD). The severity of VDD differs with age, gender and region. Females are more severely vitamin D deficient than males. Various factors contributing towards it deficiency are linked to their housing designs, religious practices, lifestyle choices and dark skin color. The increasing incidences of breast, prostate and colon cancer among this society are also raising an alarm. The presence of vitamin D receptor (VDR) and the enzyme responsible for conversion of the 25(OH)D in its active metabolite 25(OH)2D3 in extra renal tissue shows the involvement of vitamin D in other diseases like cancer, diabetes, multiple sclerosis etc. About 2000 genes related to various types of diseases are found to be regulated by VDRs. These genes possess vitamin D responsive elements (VDREs) in their promoters. Studies on population of other regions also have shown correlation with low serum levels of 25(OH)D and certain diseases So, we hypothesized that vitamin D deficiencies might cause a higher prevalence of these diseases in the Kingdom.